Relationship between chromatin configuration and in vitro maturation ability in guinea pig oocytes - Min‐Hua Yao (Wiley, 2021)
Abstract Background Germinal vesicle (GV) chromatin configurations of oocytes are proposed to be related to oocyte competence and may reflect the quality of oocyte. Currently, a limited number of published studies investigated the GV chromatin configurations of guinea pig oocytes. Objective In this study on the in vitro maturation (IVM) of guinea pig oocytes, we examined the changes in their GV chromatin configurations during meiotic progression. Methods Based on the degree of chromatin compaction, the GV chromatin configurations of guinea pig oocytes could be divided into three categories depending on whether the nucleolus‐like body (NLB) was surrounded or partly surrounded by compacted chromatin, namely the uncondensed (NSN), the intermediate type (SN‐1) and the compacted type (SN‐2). Results The percentage of cells displaying the SN‐2 configuration increased with the growth of guinea pig oocytes, suggesting that this configuration presents the potential for maturation in oocytes. Oocytes derived from larger follicle exhibited increased meiotic potential. Serum starvation affected the GV chromatin configurations of guinea pig oocytes. Conclusions Collectively, these results suggest that the SN‐2 type might be a more mature form of configuration in guinea pig oocyte, whose proportion was associated with the follicle size and susceptible to the environment (e.g. serum concentration).